Angiopoietin-like protein 3 and 4 in obesity, type 2 diabetes mellitus, and malnutrition: the effect of weight reduction and realimentation - Cinkajzlová, Anna; Mráz, Miloš; Lacinová, Zdeňka; Kloučková, Jana; Kaválková, Petra; Kratochvílová, Helena; Trachta, Pavel; Křížová, Jarmila; Haluzíková, Denisa; Škrha, Jan; Papežová, Hana; Haluzík, Martin (Nutrition & diabetes, 2018)
BACKGROUND: Angiopoietin-like proteins (ANGPTLs) 3 and 4 are circulating factors that participate in the regulation of lipid and glucose metabolism. SUBJECTS AND METHODS: We measured serum ANGPTL3 and 4 levels in 23 patients with obesity, 40 patients with obesity and type 2 diabetes mellitus (T2DM), 22 patients with anorexia nervosa (AN), 15 subjects undergoing 72-h fasting, and 12 patients with short bowel syndrome (SBS), and their changes after very-low-calorie diet (VLCD), bariatric surgery, partial realimentation, acute fasting, and parenteral nutrition in order to assess their possible role in metabolic regulations. RESULTS: Serum ANGPTL4 levels were higher in obese subjects without/with T2DM (94.50 ± 9.51 and 134.19 ± 7.69 vs. 50.34 ± 4.22 ng/ml, p < 0.001) and lower in subjects with AN relative to healthy control subjects (38.22 ± 4.48 vs. 65.80 ± 7.98 ng/ml, p = 0.002), while serum ANGPTL3 levels demonstrated inverse tendency. Nutritional status had no effect on ANGPTL3 and 4 mRNA expression in adipose tissue. Fasting decreased ANGPTL3 and increased ANGPTL4 levels, while VLCD reduced only ANGPTL3. Bariatric surgery and realimentation of AN or SBS patients had no effect on either ANGPTL. Multiple regression analysis identified BMI as an independent predictor of ANGPTL3; and BMI and HbA1c as independent predictors of ANGPTL4, respectively. CONCLUSIONS: Taken together, our data suggest that serum ANGPTL3 and 4 levels are influenced by nutritional status and fasting and could be involved in the metabolic disturbances present in obesity and AN.
Keywords: chirurgie trávicího traktu; obezita; Bariatric Surgery; hmotnostní úbytek; Humans; lidé středního věku; syndrom krátkého střeva; Angiopoietin-Like Protein 3; Female; Angiopoietin-like Proteins; výsledek terapie; lidé; Malnutrition; Diabetes Mellitus, Type 2; podvýživa; ženské pohlaví; Male; Middle Aged; angiopoetinu podobný protein 4; Treatment Outcome; bariatrická chirurgie; Angiopoietin-Like Protein 4; angiopoetinu podobné proteiny; Short Bowel Syndrome; Obesity; angiopoetinu podobný protein 3; mužské pohlaví; diabetes mellitus 2. typu; Digestive System Surgical Procedures; Weight Loss